Downtime and Maintenance System Analysis of Reverse Osmosis (RO) Unit in a Beverage Manufacturing Company - Ade Bagas Kusuma; Anggita Muhamad Maulana; Erwin Setiawan; Muhammad Rizki Abdul Aziz; Yudi Prastyo (Lentera Ilmu Nusantara, 2026)
This study aims to analyze downtime and maintenance systems in the Reverse Osmosis (RO) unit of a beverage manufacturing company. The research used a descriptive quantitative approach through direct observation, maintenance documentation, technician reports, and interviews with operators. The results showed that the RO unit experienced 31 hours of downtime during 720 hours of operation, with membrane fouling, clogged pre-treatment filters, high-pressure pump failure, and unstable water pressure identified as the main causes. The Mean Time To Repair (MTTR) was 2.58 hours, while the Mean Time Between Failures (MTBF) was 60 hours, with a machine availability rate of 95.69%. These findings indicate that although the RO unit is relatively reliable, the maintenance system still requires improvement, particularly in preventive maintenance scheduling and real-time monitoring. The implementation of PLC-based automation, PID control, and IoT-based monitoring is recommended to reduce downtime, improve operational efficiency, and maintain consistent water quality.